Photovoltaic Cell Sizing Software Development by Android Studio for Solar Powered Tube-well System - Kiu, Jeffrey; Sahdan, Mohd Zainizan (Evolution in Electrical and Electronic Engineering, 2021)
Renewable solar energy takes an important role in solving the high power demand from the rapid growth of the human population. The people who live in the rural area did not have a chance to access modern energy, where lots of them suffer from the shortage of clean water and the limited amount of power supply. In this study, a solar powered tube-well system is designed with the evaluation of working hours of the water pump motor in a day and cost for the system by considering of solar irradiation throughout the day. A software application of photovoltaic sizing calculator is designed and developed by Android Studio to simplify the calculation with the implementation of a method derived from graph analysis of daily solar irradiation and electrical performance of photovoltaic modules. The developed app named Pivee Sizinlator can calculate the number of photovoltaic modules required and the rating of other components for 2 types of off-grid systems: with and without battery. The finding of this study shows that photovoltaic system without battery requires fewer photovoltaic modules than the system with battery for the same working hours. Hence, system without battery is more cheaper as it uses fewer photovoltaic modules and have no battery. A model of stand-alone solar powered tube-well system without battery is successfully designed as the solution for the water shortage problem of people in rural areas. The final system model design would be consisting of 14 PV modules, a 1HP water pump motor and a 12V 3kW rating of inverter that can be work for 10 hours.